Taking C.A.R.E of business [videorecording] ([St. Paul, Minnesota] : StarThrower, 1999)
Truly great customer service professionals knows that to deliver remarkable customer service, you have to choose to be Connected, Attentive, Responsible and Enthusiastic (C.A.R.E). From greeting customer and gracefully managing several at once, to handling dissatisfied customers and keeping a fresh outlook at all times, this video emphasizes personal accountability as it teaches employees to actively improve their customer relations skills.
DVD format
Keywords: Customer relations; Personnel management; Employees -- Training of